Sequential Foley Catheter and Misoprostol Versus Misoprostol Alone for Induction of Labor in Postdated Pregnancy: a Randomized Controlled Trial - Thapa, Baburam Dixit; Manandhar, Tara; Sitaula, Sarita; Basnet, Tulasa (Journal of BP Koirala Institute of Health Sciences, 2020)
Introduction: Induction of labor is done with the aim of normal vaginal delivery. There are different methods; mechanical like intra-cervical Foley’s or pharmacological agents like misoprostol ordinoprostone. Objectives: To compare sequential use of Foley’s catheter and vaginal misoprostol in comparison with vaginal misoprostol only. Methods: Patients with period of gestation more than or equal to 41 weeks without any complications were assigned randomly according to computer generated randomization into sequential use ofintracervical Foley followed by vaginal misoprostol after 24 hours (sequential group) or vaginalmisoprostol only. Primary outcome was rate of normal vaginal delivery. Secondary outcomes were induction to delivery interval, maternal and fetal morbidity. Results: Rate of normal vaginal delivery in sequential group (n= 353) and misoprostol alone group(n= 356) was 71.6% and 53.3% (p < 0.001) but the time to delivery from induction is statistically more in sequential group (30.3 vs. 11.2 hours, p< 0.001). Maternal outcomes like postpartum hemorrhage, hyper-stimulation syndrome, chorioamnitis and neonatal outcomes like low Apgar score, meconium stained baby and stillbirth are similar in both the groups. Conclusions: The priming of cervix using intracervical Foley catheter before giving vaginalmisoprostol was beneficial in increasing the rate of normal vaginal delivery but it increased the induction to delivery interval.